1984
DOI: 10.1177/026309238400300201
|View full text |Cite
|
Sign up to set email alerts
|

Loudness of Pure Tones at Low and Infrasonic Frequencies

Abstract: Contours of equal loudness were determined in the frequency range 2–63 Hz and the loudness range 20–100 phon. The loudness curves run almost parallel in the infrasonic frequency range and much closer than in the audio region. Infrasound only a few dB above the hearing threshold will therefore seem loud and possibly annoying. The subjects were 20 normal hearing students aged between 18 and 25, and the psychometric method was based on maximum-likelihood estimation of psychometric functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
142
4
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(172 citation statements)
references
References 7 publications
13
142
4
3
Order By: Relevance
“…The method of constant stimuli was used for the measurement by Robinson and Dadson [2] while we used the randomized maximum likelihood sequential procedure [8,19]. Gabriel et al [21] and Takeshima et al [8] reported that PSE measured by the method of constant stimuli may be strongly affected by the level setting of variable stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of constant stimuli was used for the measurement by Robinson and Dadson [2] while we used the randomized maximum likelihood sequential procedure [8,19]. Gabriel et al [21] and Takeshima et al [8] reported that PSE measured by the method of constant stimuli may be strongly affected by the level setting of variable stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The randomized maximum likelihood sequential procedure [8,19], which is known to be robust against the range effect, was used for the measurements of equal-loudness levels. A reference stimulus and a variable stimulus were presented as a pair.…”
Section: Measurement Of Equal-loudness Levelsmentioning
confidence: 99%
“…Sie vermitteln Druck-, Berührungs-, Kitzel-und Vibrationswahrnehmungen [17]. Unterhalb 10 Hz können sogar die Schalldruckschwankungen wahrgenommen werden [8]. Körpervibrationen entstehen durch tieffrequenten Schall und Umgebungsvibrationen.…”
Section: Definition Und Wahrnehmung Von Infraschall Und Tieffrequenteunclassified
“…Es gibt darüber hinaus Hinweise auf für tieffrequenten Schall außerordent-lich sensible Personen [8] ßenordnung wie die Abmessungen der Umgebungsstrukturen liegen (z.B. Häu-ser, Räume und Brücken) [5].…”
Section: Definition Und Wahrnehmung Von Infraschall Und Tieffrequenteunclassified
“…The loudness of low-frequency noise is not especially high, because the hearing sensitivity of a human being declines at low frequencies 6) . Therefore, low-frequency noise hardly causes adverse physical effects on the auditory organs, such as noise-induced hearing loss.…”
Section: Introductionmentioning
confidence: 99%